Reactivity of cellulose reducing end in pyrolysis as studied by methyl glucoside-impregnation. (February 2016) - Matsuoka, Seiji; Kawamoto, Haruo; Saka, Shiro
Highlights: Cellulose was stabilized by impregnation of methyl β-glucoside (GlcβOMe). Cellulose reducing ends were converted into the glycosides with GlcβOMe. Polymerization of GlcβOMe was accelerated in the presence of cellulose. A mechanism via reactive glucose is proposed for the GlcβOMe polymerization. Role of cellulose reducing end in pyrolysis is discussed. Graphical abstract: Abstract: For better understanding of the roles of cellulose reducing ends during thermal degradation of cellulose and wood, cellulose samples impregnated with methyl-β-d -glucopyranoside (GlcβOMe), a simple non-reducing sugar model, were pyrolyzed under N2 at relatively low temperatures of 200–280 °C. By the impregnation, cellulose was rather stabilized against discoloration and weight-loss through converting the reducing ends into the glycosides with GlcβOMe. Alternatively, polymerization and discoloration of GlcβOMe were accelerated in the presence of cellulose. A mechanism via reducing sugars as reactive intermediates formed through hydrolysis is proposed to explain these phenomena. These information would be useful to understand the interactions between cellulose and hemicellulose in wood cell wall as well as the role of the reducing ends in cellulose thermal degradation.